Reversible Splenial Lesion Syndrome Associated with Encephalitis/Encephalopathy and Hyponatremia - Güngör, Serdal; Kılıç, Betül; Aslan, Mahmut; Özgör, Bilge (Journal of Pediatric Neurology, 2020)
Reversible splenial lesion syndrome (RESLES) is a rare occurrence with a broad clinical and radiological spectrum due to several conditions and diseases. Generally, clinical symptoms of RESLES include mildly altered states of consciousness, delirium, and seizures. RESLES can be shown in conjunction with central nervous system infections, especially in children. Hyponatremia is also described as a potential cause of reversible splenial lesions. Reversible signal changes on diffusion-weighted images are detected in patients for diagnosis. The prognosis is usually good but it depends on the underlying disease, neurological and imaging findings. Here we present two pediatric patients with RESLES accompanied by hyponatremia.
Keywords: reversible splenial lesion syndrome; hyponatremia; encephalitis